MANAGEMENT OF THE EXCELLENT CLASS PROGRAM AT SMPIT ABU BAKAR YOGYAKARTA IN THE ACADEMIC YEAR 2024–2025 - Muhammad Thorif Abdurrofi (Jurnal Eduslamic, 2025)
This study aims to describe the strategy of managing superior classes at SMPIT Abu Bakar Yogyakarta in order to improve the quality of education and student learning achievement. Superior classes are classes that are specifically designed for students who have high academic potential and require an intensive, innovative learning approach, and are supported by adequate facilities. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the strategy of managing superior classes at SMPIT Abu Bakar Yogyakarta is carried out through careful planning, organizing learning structures, implementing active teaching, and systematic evaluation. Supporting factors in the implementation of superior classes include teacher quality, parental involvement, and learning facilities. The obstacles faced include social disparities between classes, limited certain facilities, and variations in student character. The solutions implemented include teacher training, improving communication between classes, and optimizing the use of learning technology.